Perancangan Konten Kampanye Sosial untuk Membangun Citra Positif Petani - Kurniawan, Rahmat; Widiatmojo, Krisna (Program Studi Desain Komunikasi Visual, Fakultas Sains dan Teknologi, Universitas Ma Chung, 2025)
This study focuses on designing social campaign content to build a positive image of rice farmers among youth, addressing stereotypes of agriculture as dirty, exhausting, unprofitable, and low-prestige. The campaign aims to shift negative perceptions, raise awareness, and foster appreciation for rice farming while encouraging generational renewal. A qualitative approach with Design Thinking methodology was employed, encompassing empathy, definition, ideation, prototyping, and testing stages. Data were collected through farmer interviews, field observations, and relevant literature reviews. The outcome comprises 12 social campaign posters utilizing visual metaphors to construct a positive farmer image. Media and subject-matter experts validated the posters’ effectiveness in conveying messages and achieving campaign goals. Target audience feedback further indicated high acceptance and appreciation levels. The findings suggest that visually metaphorical campaigns can reshape youth perceptions, highlighting the potential of strategic communication in agricultural revitalization.